DETERMINASI KUALITAS LAPORAN KEUANGAN PADA AKUNTABILITAS KINERJA PEMERINTAH DAERAH - Feby Izami , Nandila; Farida; Hakim Purwantini, Anissa (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
The Performance Accountability Value of Government Agencies in the Magelang Regency Government can be improved through programs that support the achievement of strategic objectives, namely by increasing government performance accountability through financial statement opinions. In government agencies, financial reporting is a manifestation of performance accountability because financial statements are one of the government's responsibilities to the people for resource management and policy implementation. The Regional Apparatus Organizations of Magelang Regency were the object of research using purposive sampling techniques. The sample qualifications were employees with a minimum of one year of service and who performed accounting or financial administration functions. The test tool used was Structural Equation Modeling-Partial Least Squares. The results of the study reveal that the competence of Human Resources, Local Government Accounting Systems, and Internal Control Systems do not have an impact on the quality of financial reports. Even so, the quality of financial reports still contributes to improving performance accountability, but does not act as a mediator between the human resource competencies, SAPD, SPI and performance accountability. The implications of this research are to encourage the implementation of optimized quality financial reports and work accountability in local government